Incorporation of Silver Nanoparticle in Cellulose Nanocrystal Extracted from Eulaliopsis binata leaf to Enhance Its Antimicrobial Activity - Rajaure, Anil; K.C., Shreesa; Rijal, Sishir; Adhikari, Shreeya; Chaudhary, Sanju; Subedi, Basanta; Sigdel, Anil; Prasad, Manoj Kumar; Oli, Hari Bhakta; Bhattarai, Deval Prasad (Amrit Research Journal, 2024)
Cellulose, one of the most abundant natural biopolymers, is widely regarded as a sustainable material and is primarily found in the cell walls of plants. This study focuses on the isolation of cellulose nanocrystals from the leaves of Eulaliopsis binata. The extraction of cellulose was performed using established chemical methods, including pre-alkalization, alkalization, acetylation, and acid hydrolysis. Silver nanoparticles were prepared through a green synthesis method and subsequently impregnated into the extracted cellulose. The resulting nanoparticle-impregnated cellulose was analyzed using Fourier-transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD) techniques. An antimicrobial assessment of the silver nanoparticle incorporation into cellulose nanocrystals revealed their effectiveness against selected microorganisms.